Changes in Arctic Ocean Climate Evinced through Analysis of IPY 2007‚Äì2008 Oceanographic Observations - Stroh, J. N. (2022)
Full-depth hydrographical surveys conducted in 2007‚Äì2009 during the International Polar Year (IPY) collaboration provide an accurate snapshot of the Arctic Ocean (AO) hydrography at a time when the Arctic Ocean Oscillation (AOO) index was highest in recent record. We construct pan-Arctic temperature and salinity (T/S) reference states from these data using variational optimal interpolation and discuss some key differences between the 2007‚Äì2009 state and a similarly constructed climatology from historical 1950‚Äì1994 Russian archives. These data provide a recent, known reference state for both qualitative and quantitative future AO climate change studies. Furthermore, we present an analysis of sea-surface height (SSH) and upper-layer circulation constructed from the IPY data via 4DVar data assimilation and use them to examine circulation and freshwater source changes visible during IPY.